The Challenges of Implementing e-Voting in Elections As a New Form Agile Governance Concept in Indonesia - Marzalia, Anisya Yuli (Prosiding University Research Colloquium, 2023)
Agile governance is a novel notion in which the government is expected to be able to respond rapidly, adaptably, and to constantly changing circumstances. The advancement of time and technology has made it possible for an electronic voting system (e-Voting) to exist. It adopts the idea of agile governance and allows individuals to exercise their right to vote only with the aid of an internet connection and any digital devices they may own to increase the effectiveness and efficiency of elections. The purpose of this research is to analyze the challenges faced in implementing e-Voting as a new form of Agile Governance concept in Indonesia. This study uses qualitative methods using secondary data sources. NVivo 12 Plus software was used to handle and analyze all the data collected for this research. The researcher refers to one of the principles of agile governance, Human Focused. Based on these principles, researchers found indicators that are still a challenge in implementing e-Voting in Indonesia, namely public trust, data security, and public participation. Because of this, it is anticipated that the emergence of the notion of agile governance will lead to positive improvements in how Indonesia implements e-Voting as a new type of voting system.